AL-QARDH DALAM PRESPEKTIF AL-QUR’AN DAN HADITS SERTA HUBUNGANNYA DENGAN RIBA - Irhamsyah Putra (Sekolah Tinggi Ekonomi Islam (STEI) Ar-Risalah Ciamis, 2022)
Borrowing activities have existed throughout the history of human civilization, which in religious literature is known as Al-Qardh. Contemporary Islamic financial transactions cannot be separated from transactions that use al-qardh, the real purpose of this transaction is for social assistance and help because the repayment of the loan is only the principal without any reward in it. This study was conducted for the purpose of analyzing the qardh contract in the perspective of the Qur'an and Hadith and its relation to the concepts of debt and usury in the perception of conventional transactions. The approach used in this research is a literature study using the library research method, which is to examine some relevant literature with the theme of the study raised. The results of the study show that Al-Qardh is part of the debt (Ad-Dain), but Ad-Dain is a more general form and is not part of al-Qardh. The current transaction mechanism, both qardh and ad-dain, both have the potential to cause usury in it.